Palladium(II) and platinum(II) mixed ligand complexes of metronidazole and saccharinate or benzisothiazolinonate ligands, synthesis and spectroscopic investigation - Ali A. K. Al-Jibori; Subhi A. M. Al-Jibori; Ahmed S. M. Al-Janabi (Tikrit Journal of Pure Science)
Six palladium (II) and platinum (II) mixed ligand complexes of metronidazole (mnz) and saccharinate (sac) or benzothiazolinolate (bit) complexes of the type [ML2(mnz)2], M = Pd or Pt, L = sac or bit, have been prepared in moderate to high yield. The newly prepared complexes have been characterized by elemental (C,H,N,S) analysis, conductivity measurements, infrared and 1H-NMR spectra. Characterization data showed that the mnz ligand in all of the prepared complexes is coordinated to metal center through the imidazole nitrogen atom. The (sac) anion ligand is coordinated through the endocyclic nitrogen atom, while the (bit) anion ligand is coordinated through the nitrogen atom in the palladium complex and through the oxygen atom of the carbonyl group in the platinum complexes. The geometry of the Pd (II) and Pt (II) complexes is square planar complexes.